On the reception of Bonhoeffer – A case study of South-South dialogue - Smit, Dirk J (Stellenbosch Theological Journal, 2016)
This article, read as a paper during a consultation on South-South receptions of Dietrich Bonhoeffer, argues that the late Russel Botman, Vice-Chancellor of the University of Stellenbosch and well-known South African ecumenical theologian, in his own person already served as a living illustration of such an encounter. He read and appropriated Bonhoeffer as a South African theologian, but in discussion and engagement with the work of several Latin American figures, including people who in different ways also read and appropriated Bonhoeffer. The article briefly shows how Botman developed three motifs that were central to his own life and thought by engaging a variety of Latin American figures – amongst others Leonardo Boff, Paolo Freire, Jon Sobrino, Juan Luis Segundo, Rubem Alves, Julio de Santa Ana, and Enrique Dussel – but always with a view also to Bonhoeffer, up to the point where it becomes difficult to distinguish any longer between the voices of Bonhoeffer, the voices of these thinkers from the South, and his own voice. The three motifs deal respectively with his concern for the next generation, his belief in imagination and hope, and his commitment to sociality and community.